Background Reduction and Energy Calibration of NaI(Tl) Detector - جبور جبور; ملحم جهاد; عبد السلام حمدي (Latakia University Journal -Basic Sciences Series, 2021)
In this work, a NaI(Tl) detector has been calibrated, and the equation that describes the relationship between energy and the channels takes the form of a straight line given as: Techniques for reducing background radiation were studied in the Nuclear Physics Laboratory at Tishreen University, where this work performed, using two methods of shielding: The traditional method. The graded shield method. The results obtained indicate that: 1-The overall count rate decreased when surrounding the detector with the lead shield (traditional method), as the count rates decreased in almost all channels (all energy peaks) using the lead shield. 2- In the graded shield method, count rates increased at several energy peaks of interest in gamma-ray spectroscopy, particularly in the (0-500) keV range; The region in which the gamma-ray backscattering effect predominates. While the graded shield method is not suitable for the lead shields of low thicknesses because the complications resulting from it are more than the reduction due to it, the traditional method is better with small thickness shields, and the minimum radioactivity (MDA) value can be improved according to the its equation by increasing measurement time T. Keywords: Gamma ray, background radiation, background radiation reduction, NaI(Tl) detector, energy calibration, gamma ray spectroscopy, passive shielding of the gamma-ray detectors.